Model pendidikan seks melalui pendekatan pedagogi kritis bagi remaja di Rifka Annisa Women’s Crisis Center - Salsabela, Ristama Fitria; Pramono, Didi (Universitas Negeri Malang, 2025)
A model of sex education through a critical pedagogy approach for adolescents at Rifka Annisa Women’s Crisis Center The research aims to analyze the sex education model through Paulo Freire’s critical pedagogy approach for adolescents in Rifka Annisa and identify its impact. This research uses descriptive qualitative methods with observation, interviews, and documentation data collection techniques. The results showed that the models and forms of sex education activities for adolescents in Rifka Annisa are the Youth Class Community Forum, RGTS (Rifka Annisa Goes to School), RGTS by Order, RGTS by Project, and media campaigns. Sex education methods using the critical pedagogy approach are serial discussions, art, and reflective methods. The serial discussion method is a discussion with a different theme for each meeting that is still continuous. The art method is a creative and interesting medium used for sex education, including music, graphic design, and performing arts. The following method is the reflective method, which is a process of deepening, realizing, and reflecting on the material, experiences, and life around the participants. Sex education activities in Rifka Annisa that use these three methods impact changes in perspective, changes in behavior, and critical awareness of participants. Penelitian ini bertujuan untuk menganalisis model pendidikan seks melalui pendekatan pedagogi kritis Paulo Freire bagi remaja di Rifka Annisa dan mengidentifikasi dampaknya. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa model dan bentuk kegiatan pendidikan seks bagi remaja di Rifka Annisa adalah Forum Komunitas Kelas Remaja, RGTS (Rifka Annisa Goes to School) RGTS by Order dan RGTS by Project, dan media campaign. Metode pendidikan seks yang menggunakan pendekatan pedagogi kritis yaitu diskusi serial, metode seni, dan metode reflektif. Metode diskusi serial merupakan diskusi dengan tema yang berbeda setiap pertemuan namun tetap berkesinambungan. Metode seni merupakan media kreatif dan menarik yang digunakan sebagai bentuk pendidikan seks meliputi musik, desain grafis, dan seni pertunjukan. Metode selanjutnya adalah metode reflektif merupakan proses pendalaman, penyadaran, dan merefleksikan materi, pengalaman, dan kehidupan di sekitar peserta. Kegiatan pendidikan seks di Rifka Annisa yang menggunakan ketiga metode tersebut berdampak untuk perubahan perspektif, perubahan perilaku, dan kesadaran kritis peserta.